P-76 Methadone prescribing and outcomes – a service evaluation to review changes in practice. (20th March 2022) - Pitsillides, Constantina; Ali, Maimoona; Evans, Hayley; Nicholson-Lailey, Anna; Fingas, Samuel; Davies, James
Abstract : Background: Methadone is a synthetic opioid which has actions on both mu and NMDA receptors and can be used in pain management. A service evaluation on the use of methadone was initially conducted in 2013. This service evaluation was repeated. The aim was to review how methadone was being used and if titration methods had changed. Methods: Prospective data was collected from patients who were initiated on methadone in Sheffield (n=21) and Doncaster (n=1). The data collected included diagnosis, indication for methadone, method of titration, pain scores and adverse effects. Methods for initiating methadone included stop-and-go (SAG), addition (ADD) and cross-titration (CT). Results: 22 inpatients were prescribed methadone over a ten-month period. In 2013, initiating methadone using SAG was seen in 72% patients but in 2021, CT was the preferred method (91%). Pain scores on average (out of ten) reduced from 7.2–3.6 which is similar to previous results. The median daily background oral morphine equivalent dose prior to methadone initiation was 165 mg (range 120–800 mg) and had reduced to 90 mg (range 0–400 mg) on day five. 50% patients had an ECG prior to commencing methadone, (92% in the 2013 review) with no documented QTc prolongation on a day six ECG. The median background dose of methadone on death or discharge was 15 mg (range 8 mg-45 mg). Conclusions: The method used most frequently for introducing methadone has changed to CT. This could be due to a change in practice following the previous service evaluation as adverse effects were most seen with SAG (2 patients required naloxone for respiratory depression). Overall, the methadone doses used were small to moderate achieving reductions in overall opioid dosing and a perceived benefit in pain control. The reduction in rate of initial ECG monitoring of QTc interval and its clinical significance will be discussed at our departmental audit meeting.